O mestrado profissional em ensino de matemática e o desenvolvimento profissional de professores: um desafio institucional - Cevallos, Ivete (2011)
This study aims to investigate and analyze the contributions of the Professional Masters in Teaching of Mathematics, PUC / SP for the professional development of teachers of Basic Education.To this end, we resort to theoretical references grounded, especially, by studying the following authors: Marcelo (2009); Ibernon (2007); Day (2001); Ponte (1998) e Gonçalves (2009); Schön (2000); Perrenoud (2004); Zeichner (2004); Beillerot (2004) e Lüdke (2005-2007-2009), that allows us to analyze the professional development of the egress teacher, taking into account a training supported in practice and in producing a search for understanding the learning and teaching process of mathematics. These readings allowed the clarification of concepts as well as indicated the starting point of this work. Besides, they brought valuable contributions to discussions on data analysis Another direction of study was to highlight the policies of the Graduate courses in professional mode in Brazil bringing what has been discussed about the regulation of Ordinances. The methodological research process unfolds within a qualitative investigation course that uses a case study.The research was developed in two phases. In the first phase, 46 egresses of the Professional Masters participated as research subjects, when the questionnaires were applied and, second, interviews were conducted with six egresses and two teachers of the Graduate Program. As a result of this process of reflection, the data showed that the contributions of the course for the professional performance of the graduates are strongly supported in the relationship shared with peers, with trainers from the discussions and readings of the theorists, and research and reflect that triggers a systematic thinking about the teacher's work culminating in this way in changing attitudes of the egresses face to their performances, when they became more inquisitive and more aware of their practices developed in the context of the classroom. It is expected to collaborate with further discussion on the training of teachers, since they improve the quality of teaching is a flag defended today by governments, educators and education experts